The role of microstructure on wear mechanisms and anisotropy of additively manufactured 316L stainless steel in dry sliding - Mohanad Bahshwan; Connor W. Myant; Tom Reddyhoff; Minh-Son Pham (Materials & Design, 2020)
Wear control, which relies on understanding the mechanisms of wear, is crucial in preserving the life of mechanical components and reducing costs. Additive manufacturing (AM) techniques can produce parts with tailored microstructure, however, little has been done to understand how this impacts the mechanisms of wear. Here we study the impact of initial grain arrangement and crystal orientation on the wear mechanisms of austenitic stainless steel (SS) in dry sliding contact. Specifically, the anisotropic sliding wear behavior of as-built, AM-ed 316L SS is compared against annealed, wire-drawn counterparts. We describe, in-detail, how the sliding wear mechanisms of delamination, abrasion, oxidation, and plastic deformation are attributed to the initial surface microstructure under different loading conditions using a number of techniques. This new understanding sheds light on how different AM-induced microstructures affect wear, thereby allowing for better utilization of this technology to develop components with enhanced wear properties.